P129 Role of telomere length within the complex relationship between genetic traits and environmental/occupational exposures in bladder cancer risk. (1st September 2016) - Pavanello, Sofia; Mastrangelo, Giuseppe; Campisi, Manuela; Carta, Angela; Arici, Cecilia; Porru, Stefano
Abstract : Introduction: Shorter telomere length in blood lymphocytes (LTL) is associated with bladder cancer (BC) risk and with lower patient survival. How these relationships are modulated by genetic traits, environmental and occupational risk factors for BC is still at early stages of investigation. Objectives: This study assesses the association of LTL with BC and its modulation by genetic polymorphisms, environmental and occupational risk factors, within the framework of a larger hospital-based case/control study. Methods: Data were collected on lifetime smoking (pack years-PY), coffee and alcohol drinking, diet, occupations with particular reference to exposure to aromatic amines (AAs) and polycyclic aromatic hydrocarbons (PAHs). LTL was measured by PCR in 96 cases and 94 controls. Cumulative exposure (CE), time since first exposure and last exposure to AAs and PAHs, lymphocytes DNA adducts, multiple genetic polymorphisms were determined. The complex relationships, including direct and indirect effects of each variable, were appraised using structural equation modelling (SEM) analysis. Results: A direct relationship was found between shortened LTL and BC risk (p < 0.0001). Shortened LTL was negatively associated with age (p < 0.0001), DNA adducts (p < 0.019), alcohol intake (p < 0.021) and positively associated with coffee (p < 0.016), MPO (p < 0.028) and XRCC2 (p < 0.048). CE to PAHs and AAs, PY and NAT2 were not associated with shortened LTL. Discussion and Conclusions: We found that LTL erosion associates with BC risk, strengthening the evidence of a relevant role of LTL in bladder carcinogenesis. The literature findings regarding age and LTL were confirmed. The new relevant findings are that LTL attrition associates, at the moment of diagnosis, with DNA adducts, alcohol, and is modulated by some genetic polymorphisms, while coffee is positively associated. Further studies in larger populations should investigate the complex interrelationships among LTL, environmental and occupational variables, genetic endpoints especially taking into account some clinical and prognostic parameters along the course of BC.